CANINE ECTOPIC TREATMENT WITH FIRST MOLAR EXTRACTION - Angelica Margo; Erwin Siregar (Journal of Dentistry Indonesia, 2015)
Decision to extract or not and the type of tooth must be analyzed carefully in orthodontic treatment. Preferable tooth to be extracted was the tooth with large caries or restoration. Usually the type of tooth to be extracted was second molar (if the third molar appears), incisor, first molar, and combination of several teeth. Orthodontic treatment with molar extraction is more difficult to treat and the result is usually compromise. There are several considerations in extracting first molar such as tooth with large caries or restoration, hypoplasia, periapical disease, large discrepancy, high maxilla-mandibular plane angle, and cases with anterior open bite. Nowadays, orthodontic cases with molar extraction do not prolong the treatment time compared to premolar extraction case, but the anchorage system must be considered carefully. The present case was treated with extraction of first molar to solve anterior crowding with maximum anchorage at the upper jaw and using Nance Holding Appliance.